A Novel Modeling Approach to Quantify the Influence of Nitrogen Inputs on the Oxygen Dynamics of the North Sea - Große, Fabian; Kreus, Markus; Lenhart, Hermann-Josef; Pätsch, Johannes; Pohlmann, Thomas (Frontiers in Marine Science, 2017)
Oxygen (O2) deficiency , i.e., dissolved O2 concentrations below 6mgO2L-1, is a common feature in the southern North Sea. Its evolution is governed mainly by the presence of seasonal stratification and production of organic matter, which is subsequently degraded under O2 consumption. The latter is strongly influenced by riverine nutrient loads, i.e., nitrogen (N) and phosphorus (P). As riverine P loads have been reduced significantly over the past decades, this study aims for the quantification of the influence of riverine and non-riverine N inputs on the O2 dynamics in the southern North Sea. For this purpose, we present an approach to expand a nutrient-tagging technique for physical-biogeochemical models – often referred to as ‘trans-boundary nutrient transports’ (TBNT) – by introducing a direct link to the O2 dynamics. We apply the expanded TBNT to the physical-biogeochemical model system HAMSOM-ECOHAM and focus our analysis on N-related O2 consumption in the southern North Sea during 2000–2014. The analysis reveals that near-bottom O2 consumption in the southern North Sea is strongly influenced by the N supply from the North Atlantic across the northern shelf edge. However, riverine N sources – especially the Dutch, German and British rivers – as well as the atmosphere also play an important role. In the region with lowest simulated O2 concentrations (around 56°N, 6.5°E), riverine N on average contributes 39% to overall near-bottom O2 consumption during seasonal stratification. Here, the German and the large Dutch rivers constitute the highest riverine contributions (11% and 10%, respectively). At a site in the Oyster Grounds (around 54.5°N, 4°E), the average riverine contribution adds up to 41%, even exceeding that of the North Atlantic. Here, highest riverine contributions can be attributed to the Dutch and British rivers adding up to almost 28% on average. The atmospheric contribution results in 13%. Our results emphasize the importance of anthropogenic N inputs ans seasonal stratification for the O2 conditions in the southern North Sea. They further suggest that reductions in the riverine and atmospheric N inputs may have a relevant positive effect on the O2 levels in this region.